ATG3 Is Important for the Chorion Ultrastructure During Oogenesis in the Insect Vector Rhodnius prolixus - Santos, Anna; Ramos, Isabela (Frontiers in Physiology, 2021)
In insects, the last stage of the oogenesis is the choriogenesis, a process where the multiple layers of the chorion are synthesized, secreted, and deposited in the surface of the oocytes by the follicle cells. The chorion is an extracellular matrix that serves as a highly specialized protective shield for the embryo, being crucial to impair water loss and to allow gas exchange throughout development. The E2-like enzyme ATG3 (autophagy related gene 3) is known for its canonical function in the autophagy pathway, in the conjugation of the ubiquitin-like ATG8/LC3 to the membranes of autophagosomes. Although the ATGs were originally described and annotated as autophagy related genes, it is now observed that ATGs often accumulate non-autophagic functions. Here, we found that Rhodnius prolixus ATG3 is highly expressed in the ovaries of the adult vitellogenic females. Parental RNAi silencing of ATG3 resulted in a 15% decrease in the oviposition rates of silenced females and in the generation of unviable F1 eggs. ATG3-silenced F1 eggs are small and present one specific phenotype of altered chorion ultrastructure, observed by high resolution scanning electron microscopy. The amounts of the major chorion proteins Rp30, Rp45, Rp100 and Rp200 were decreased in the silenced chorions, as well as the readings for dityrosine cross-linking and sulfur, detected by fluorescence emission under ultraviolet excitation and X-ray elemental detection and mapping. Altogether, we found that ATG3 is important for the proper chorion biogenesis and, therefore, crucial for this vector reproduction.